2016
DOI: 10.1590/1414-431x20165409
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system blockers regulate the metabolism of isolated fat cells in vitro

Abstract: Due to the presence of the renin-angiotensin system (RAS) in tissues and its specific influence on white adipose tissue, fat cells are possible targets of pharmacological RAS blockers commonly used as anti-hypertensive drugs. In the present study, we investigated the effects of different RAS blockers on fat cell metabolism, more specifically on lipolysis, lipogenesis and oxidation of energy substrates. Isolated primary adipocytes were incubated with different RAS blockers (aliskiren, captopril and losartan) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…For example, Kalupahana et al demonstrated that the major sources of oxidative stress in adipose tissues are the activation of membrane-associated NADPH-oxidases by Ang II stimulation in transgenic mice overexpressing angiotensinogen in adipose tissues, and they demonstrated that RAS overactivation causes systemic insulin resistance [ 14 ]. In the in vitro study of Caminhotto et al, lipolysis, lipogenesis and glucose oxidation capacities of different RAS blockers (aliskiren, captopril, and losartan) were investigated through co-incubated isolated primary adipocytes and different RAS blockers in vitro for 24 h [ 48 ]. Concerning the effect of aliskiren treatment, aliskiren treatment only increased glucose oxidation capacities following insulin stimulation in fat cells, which implies that in vitro aliskiren treatment has an improvement of oxidative stress in isolated primary adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kalupahana et al demonstrated that the major sources of oxidative stress in adipose tissues are the activation of membrane-associated NADPH-oxidases by Ang II stimulation in transgenic mice overexpressing angiotensinogen in adipose tissues, and they demonstrated that RAS overactivation causes systemic insulin resistance [ 14 ]. In the in vitro study of Caminhotto et al, lipolysis, lipogenesis and glucose oxidation capacities of different RAS blockers (aliskiren, captopril, and losartan) were investigated through co-incubated isolated primary adipocytes and different RAS blockers in vitro for 24 h [ 48 ]. Concerning the effect of aliskiren treatment, aliskiren treatment only increased glucose oxidation capacities following insulin stimulation in fat cells, which implies that in vitro aliskiren treatment has an improvement of oxidative stress in isolated primary adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the effect of aliskiren treatment, aliskiren treatment only increased glucose oxidation capacities following insulin stimulation in fat cells, which implies that in vitro aliskiren treatment has an improvement of oxidative stress in isolated primary adipocytes. Also, Caminhotto et al suggested that the in vivo effects of aliskiren treatment on adipose oxidative stress merit to be further clarified [ 48 ]. In our in vivo study, the data showed that aliskiren treatment reduced visceral adipose Ang II and NOX isoforms expressions, increased adipose SOD activity, and diminished adipose lipid peroxide in fructose-fed rats, which indicated that in vivo aliskiren treatment had the improvement of oxidative stress in visceral adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lack of the effect of losartan on slow force changes in the myocardium of monocrotaline-treated rats may reflect either the silencing of angiotensin secretion or augmented activation of AT 1 receptors under pathological remodeling of cardiac cell in this model of right ventricular failure. A direct effect of losartan on metabolic processes like glucose oxidation, as recently reported in fat cells (Caminhotto et al 2016), is hardly believed in the muscles because of the great suppression of SFR in normal myocardium under perfusion by losartan and the absence of this effect in "failing" muscles. Authors note that our ambient conditions were out of physiological.…”
Section: Discussionmentioning
confidence: 95%